RESILIENCE IN CHILDREN CAUGHT IN DRUGS CASE IN PALEMBANG CLASS I LPKA WITH ISLAMIC PSYCHOTRAPHY APPROACH - Rama Revanza; Ira Novri Anggraini; Kartika Cantamala; Zakiah Rani Amanda; Lidia; Peri; Dicky Wandira Aditya Putra; Nissya Novi Andini; Ridha Setya Dinta; Irfa Farhatul Maula; Fasya Annisa; Siti Balqis Lubis; Audy Ananda; Asni; Albert Haryadi (CV. Doki Course and Training, 2023)
Narcotics cases are the biggest cases in Indonesia, both users or dealers and dealers. Narcotics users in LPKA 1 Palembang are dominated by teenagers so that the psychological condition resulting from the use of narcotics is prone to experiencing depression, stress and excessive anxiety. The purpose of this study was to find out and overcome resilience in children who were caught in drug cases at LPKA 1 Palembang with an Islamic psychotherapy approach. The method used is a qualitative method with a qualitative descriptive approach and uses Islamic psychotherapy interventions. Research subjects amounted to 3 people. Data collection was obtained using interviews and observations. Data analysis uses descriptive and deductive techniques (describes and describes all problems clearly and in detail). The results of this study show that through Islamic psychotherapy intervention, namely gestalt therapy, to overcome the attitudes of children who are caught in drug cases in Class I LPKA Palembang. Islamic psychotherapy interventions carried out at LPKA Class I Palembang on narcotic addicts were able to build good resilience. The resilience possessed by Narcotics addicts cannot be separated from the learning process obtained during the detention period.